Planning in Enhancing Higher Order Thinking Among Science’s Students: The Future of Green Technology - Ab Razak, Nurul Syahinaz binti; Kamarudin, Nurzatulshima binti (Jurnal Pendidikan Bitara UPSI, 2021)
The initiatives of green technology module through curriculum is an anticipated outcome of the continuous integration of Science, Technology, Engineering and Mathematics (STEM) into the syllabus of educational curriculum in schools. This attempt is among the accomplishments by the Ministry of Education in promoting enthusiasm and engagement of students in STEM. Critical thinking, innovating thinking, problem solving and scientific thinking are the components that should be present in STEM education to build up students’ higher order thinking skills (HOTS). In this concept paper, green technology implementation along the process of learning which could build up students’ thinking skills is discussed. According to the literature, there are problems that arise due to the lack of understanding to implement green technology that would eventually impact STEM education. Nevertheless, in implementing it, numerous aspects and disputes have to be put into consideration. In this study, the researchers will find practical strategies that are usable in building up higher order thinking skills of students in which they will experience a number of hands-on green projects.